Review: Utilization of Fe and Ni Green Nanoparticles in Waste Treatment to Enhance Pollutant Degradation Efficiency and Sustainability - Riny Yolandha Parapat; Irsan Asfari Khoirin; Najla Septariani; Reygina Katon Cahyani; Sabrina Putri Nurlian (Rekayasa Hijau : Jurnal Teknologi Ramah Lingkungan, 2025)
The growing need for sustainable and effective pollutant degradation technologies has sparked interest in green nanotechnology as a viable solution. This review emphasizes the use of non-noble metal green nanoparticles in waste treatment applications, showcasing their ability to improve pollutant degradation efficiency while ensuring environmental sustainability. Key topics covered include synthesis methods that employ natural and eco-friendly reducing agents, the physicochemical characteristics of non-noble metal nanoparticles, and their catalytic mechanisms in a variety of waste treatment processes. Comparative studies highlight the benefits of Fe and Ni, such as their cost-effectiveness, abundance, and lower environmental impact. This paper also presents case studies that demonstrate the breakdown of organic pollutants and heavy metals show the practical use of these materials. Challenges such as stability, scalability, and potential environmental risks are thoroughly analyzed, along with prospects to overcome these obstacles. This review seeks to provide a detailed understanding of how Fe and Ni green nanoparticles contribute to the advancement of sustainable waste treatment technologies.Keywords: green nanotechnology, fe and ni nanoparticles, waste treatment, green nanocatalyst, environmental sustainability.